Synthesis of Chitosan Sulfate From Crab (Scylla serrata) and its application as adsorbent - Salmahaminati, Salmahaminati (Universitas Negeri Yogyakarta, 2020)
Synthesis of chitosan sulfate from crab (Scylla Serrata) shell and its application as Remazol Yellow FG dye adsorbent has been studied. This experiment was conducted to study the effectiveness of chitin from crab shell to be converted into chitosan sulfate and to study the adsorption of chitosan sulfate by Remazol Yellow FG dye.Â Isolation of chitin from crab shell was done by deproteination and demineralization process. Chitin had been converted into chitosan using demineralization process. Chitosan sulfate was made by reacting chitosan with 1 M ammonium sulfate solution. Characterizations of the chitosan are involving determination of degree of deacetylation. Functional group of chitin, chitosan and chitosan sulfate were determined by FTIR spectroscopy. The dye adsorption of chitosan sulfate was analyzed with UV-Vis spectroscopy. The result showed that rendement of chitin, chitosan and chitosan sulphate were 28.57%, 52.5% and 92%. The degree of deacetilation of chitin and chitosan were 80 â€“ 90% and 70 â€“ 80%. Remazol Yellow FG was adsopr 76.5%.